Herbal medicine for treatment of children diagnosed with COVID-19: A review of guidelines. (May 2020) - Ang, Lin; Lee, Hye Won; Kim, Anna; Lee, Ju Ah; Zhang, Junhua; Lee, Myeong Soo
Abstract: This review aimed to summarize and analyze the pattern identification (PI), herbal formulae, and composition of herbs provided by recent guidelines for the treatment of pediatric COVID-19. Seven data sources were reviewed until March 25, 2020. We analyzed the herbal formulae included in the guidelines and performed a network analysis to identify the frequency of herbs recommended in the herbal formulae. All 3 guidelines were provincial guidelines from China. Our results showed that there were 4 stages, 12 PIs, and 13 herbal formulae recommended by the provincial guidelines. These herbal formulae included a total of 56 herbs. Based on our network analysis, Scutellariae Radix was paired with Artemisiae Annuae Herba in one cluster. In another cluster, Armeniacae Semen was paired with Coicis Semen and Ephedrae Herba was paired with Gypsum Fibrosum. This review serves as a reference for the use of traditional medicine in the treatment of pediatric COVID-19. Highlights: This review summarizes and analyze the herbal formulae, and the composition of herbs provided by recent guidelines for the treatment of pediatric COVID-19. Of the total of 56 herbs recommended, the herb Armeniacae Semen was one of the highly use for the treatment for pediatric COVID-19. This review can be used as a reference for the traditional medicine treatment of pediatric COVID-19.